As a man thinketh - Allen, James, 1864-1912 (Salt Lake City, UT : Project Gutenberg, 2003)
"As a man thinketh" by James Allen is a self-help book published in 1903. Drawing inspiration from a biblical proverb, Allen explores the power of thought and how it shapes our lives and circumstances. He argues that each person holds the key to their conditions through their own thinking, and by working patiently on their thoughts, they can remake their life and transform their circumstances. The book aims to be simple and practical, offering methods readers can easily apply. (This is an automatically generated summary.)
Thought and character -- Effect of thought on circumstances -- Effect of thought on health and the body -- Thought and purpose -- The thought factor in achievement -- Visions and ideals -- Serenity.
Wikipedia page about this book: https://en.wikipedia.org/wiki/As_a_Man_Thinketh
Release date is 2003-10-01
Produced by Charles Aldarondo. HTML version by Al Haines.
Keywords: Conduct of life; New Thought